2022
DOI: 10.5397/cise.2021.00717
|View full text |Cite
|
Sign up to set email alerts
|

YouTube as a source of patient education information for elbow ulnar collateral ligament injuries: a quality control content analysis

Abstract: Background: While online orthopedic resources are becoming an increasingly popular avenue for patient education, videos on YouTube are not subject to institutional or peer review. The purpose of this cross-sectional study was to evaluate the quality of YouTube videos for patient education in ulnar collateral ligament (UCL) injuries of the elbow. Methods: A search of the keywords “ulnar collateral ligament,” “ulnar collateral ligament injury,” “medial collateral ligament,” and “medial collateral ligament injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
7
1
1
Order By: Relevance
“…12,13 Yu et al previously evaluated YouTube videos for UCL injuries and found that DISCERN did vary by source, with physician videos having higher scores than those made by nonphysicians. 16 The current study found no difference in DISCERN score based on video source. One possible explanation for this is that some physician videos were primarily surgical technique videos.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…12,13 Yu et al previously evaluated YouTube videos for UCL injuries and found that DISCERN did vary by source, with physician videos having higher scores than those made by nonphysicians. 16 The current study found no difference in DISCERN score based on video source. One possible explanation for this is that some physician videos were primarily surgical technique videos.…”
Section: Discussioncontrasting
confidence: 57%
“…14,17,[23][24][25][26][27] Prior evaluation of YouTube videos on UCL injuries revealed 78% of videos were low quality; however, videos on UCLR were not specifically studied. 16 Building on these findings, the current study demonstrates that most YouTube videos for UCLR do not offer patients with high-quality information regarding the procedure.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…► capsulite adesiva ► bursite ► gravação em video ► redes sociais ► internet video source/uploader, (5) content type, (6) days since upload, (7) view rate (views/day), and (8) likes. The authors and uploaders of the videos were classified into seven groups: (1) academic (related to authors or uploaders affiliated with research groups, universities, or colleges), ( 2) physician (related to independent physicians or groups of physicians without research or academic affiliation), (3) non-physicians (healthcare workers other than licensed medical doctors), (4) trainer, (5) medical source (content or animations from health websites), ( 6) patient, and (7) commercial.…”
Section: Palavras-chavementioning
confidence: 99%
“…Several studies have shown evidence that the educational quality of YouTube videos dealing with orthopaedic diseases is inadequate. 1 2 3 6 7 8 Only one study in the literature examines youtube videos related to adhesive capsulitis. 9 The results of this study were consistent with those of other research.…”
Section: Introductionmentioning
confidence: 99%